413 The epithelial–mesenchymal transition protects heterogeneous breast tumors against immune attack in multiple species - Kimaya Bakhle; Shiney Chandraganti; Brian Feng; Brenda Ramos-Villanueva; Andrew Miller (Journal of Clinical and Translational Science)
Objectives/Goals: Our aim was to identify how the epithelial–mesenchymal transition shields heterogeneous breast tumors against immune attack. Additionally, we endeavored to understand whether our findings were conserved in canine mammary tumors as a translational model for human breast tumors. Methods/Study Population: To understand interactions between quasi-mesenchymal (qM) tumor cells, epithelial (E) tumor cells, and immune cells within heterogeneous breast tumors, we utilized a preclinical mouse model established in our lab. In this system, we can precisely control the proportions of E and qM tumor cells within tumors and study what immune cells infiltrate these tumors in response, using flow cytometry and immunofluorescent staining. Using this model, we have also established cell lines to study E and qM tumor cells in vitro. Finally, we used immunohistochemistry to label immune cells in canine mammary tumors and quantified the presence of these cells in relation to the expression of epithelial and mesenchymal cellular markers. Results/Anticipated Results: We observed that immune suppression within heterogeneous mammary tumors is driven by local, rather than systemic, effects of quasi-mesenchymal (qM) tumor cells. The presence of systemic qM-derived factors does not alter immune cell infiltration nor sensitivity to immunotherapy of epithelial (E) tumors. Furthermore, I found that the local activity of qM-derived factors within heterogeneous tumors induces immune-suppressive changes in surrounding E cells, which protects them against immune attack. Finally, I found that canine mammary tumors with higher proportions of qM tumor cells assemble an immune-suppressive tumor microenvironment, highlighting the translational potential of our findings. Discussion/Significance of Impact: We identified that the epithelial–mesenchymal transition induces immune-suppressive changes in heterogeneous tumors. These findings may reveal novel therapeutic targets for treatment of refractory tumors. Our findings in canine tumors suggest that these mechanisms are conserved across species.